Digital Transformation of Health Services in Indonesia through the Utilization of Artificial Intelligence, Big Data, and Telemedicine: Systematic Literature Review-VOSviewer - Salihati Hanifa; Kurniawan Erman Wicaksono (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Indonesia's healthcare system continues to face significant challenges in delivering equitable services across diverse and remote regions. The digital transformation of healthcare—through the integration of Artificial Intelligence (AI), big data, and telemedicine—offers promising solutions to overcome disparities in access, infrastructure, and service delivery. This study aims to comprehensively analyze global and national research trends related to the digital transformation of healthcare using a Systematic Literature Review (SLR) approach, supported by bibliometric analysis through the VOSviewer software. Following the PRISMA protocol, a total of 30 relevant articles published between 2020 and 2025 were identified and analyzed. The network and overlay visualizations generated reveal four major thematic clusters: digital transformation and service quality, big data and pandemic response, AI and data privacy, and community engagement in digital health services. Overlay visualization also shows a clear shift in research focus—from early pandemic responses toward system optimization, ethical governance, and technological inclusivity in recent years. The findings highlight that digital healthcare transformation has increasingly evolved from emergency responses to COVID-19 into a strategic framework for long-term system improvement. Moreover, AI and big data have played pivotal roles in enhancing diagnostics, predicting outbreaks, and improving resource allocation. However, concerns related to privacy, digital literacy, and unequal technological access remain prominent. The study concludes that the integration of AI, big data, and telemedicine not only enhances healthcare efficiency but also requires strong regulatory frameworks, infrastructure readiness, and public engagement. Future research should incorporate co-citation and cross-country comparative analyses to enrich the understanding of digital health transformation in a global context, especially in low- and middle-income countries like Indonesia.